Self-reported sulphonamide hypersensitivity reactions in adults living in Ibadan, Nigeria: Across-sectional, community-based study (2015)
Background: Documentation of adverse drug reactions (ADRs) is critical to a safe health delivery system. The aim of our study was to explore the prevalence of self-reported sulphonamide hypersensitivity reactions in a community based sample of the general population in Ibadan, Nigeria. We also examined sociodemographic factors associated with ADRs in the sample. Patients and Methods: The study was cross-sectional in design with study sites in urban, semiurban, and rural settlement areas. Pretested questionnaires were administered on a one-on-one basis by trained interviewers. Frequency tables and percentages were computed for various levels of the variables. Chi-square test was used to assess the relationship between sulphonamide hypersensitivity and variables such as sociodemographic characteristics of respondents, respondents' knowledge of drugs, as well as drug sources. Variables found to be significantly associated with sulphonamide hypersensitivity were further investigated using multiple logistic regressions analysis Results: Out of the 1062 respondents, 15.5% reported hypersensitivity to sulphonamides with skin reactions being the most prevalent. The proportion reporting ADRs was significantly higher among respondents with tertiary education (23.1%) than any other level of education (P = 0.008). In addition, individuals who were very knowledgeable about drug use (odds ratio[OR]: 2.07; 95% confidence interval [CI]: 1.15–3.73) and persons who got drugs from hospitals (OR: 2.00; 95% CI: 1.10–3.65) were more likely to report ADRs than those who were ignorant about drugs and those who purchased drugs from open markets, respectively. Conclusion: Prevalence of sulphonamide hypersensitivity is high among respondents, and ADRs is likely to be reported by people who are knowledgeable about drug use.